Kebakaran hutan di Indonesia: penyebab, biaya dan implikasi kebijakan - Tacconi, L. (Center for International Forestry Research, 2003)
Fires are considered a potential threat to sustainable development for their direct impacts on ecosystems, their contribution to carbon emissions, and impacts on biodiversity. In 1997/98, Indonesia had the most severe fires worldwide, and smoke haze pollution recurs yearly. The fire-related policy problems are defined as smoke haze pollution, forest degradation and deforestation, and impacts on the rural sector. Some of the apparent major causes of the problems are identified. The estimate of area affected by fires in 1997/98 is revised from 9.7 million hectares to 11.7 million hectares. The fires that resulted in forest degradation and deforestation caused economic costs in the range of $1.62-2.7 billion. The costs of smoke haze pollution were in the range of $674-799 million, and probably higher because estimates for the economic impacts on Indonesian business activities were not available. The valuation of costs associated with carbon emissions indicates that these may amount to as much as $2.8 billion. The revised estimates of economic costs from fires and smoke haze are still substantial and point to significant problems to be addressed to avoid similar impacts. Detailed policy recommendations are presented.